Digital Public Relations Tools For Effective Public Library Services - Urhiewhu, Lucky Oghenetega (International Journal of Knowledge Content Development & Technology, 2025)
In this study, the researcher investigated Digital Public Relations Tools For effective Public Library Services in South-West, Nigeria. The study aims to know the nexus between public relations tools such as social media or electronic resources and effective services rendered by public librarians to meet users, especially in this era where by majority of users are moved into technology instead of the traditional ways of using print resources. The study adopted a correlation research design which used simple and multiple linear methods. The population are professional and para-professional library staff in public libraries in the six states of South West, Nigeria. The total number is one hundred forty-four library staff. The researcher involved the whole population as a sample by using census sampling techniques. The instruments (rating scales) were used to collect data in this study. The Pearson Product Moment Correlation statistics were used to answer two research questions. The findings of the study are that; there is a moderate, positive and significant relationship between, electronic tools and public library services. There is a low, positive and significant relationship between social media tools and public library services. From the aforementioned findings the researcher that the library management should ensure that all the public relations tools identified in this study should be applied in public libraries to enhance service delivery. The study concluded that public relations tools social media & electronic media) are significantly related to effective public library services in South-West, Nigeria. The research was original work carried out by the researcher, it is a part of his PhD thesis.